A study of corrosion behaviour of typical pump materials under sea water - Mao, Terrence Wei Quan (2018)
Electrical submersible pumps are becoming increasingly popular in the oil and gas industry because of their ability to extract large amount of fluids deep underground. During the extraction process, the pump system is subjected to many corrosive elements. Corrosion is a very big economic problem in the oil and gas industry and it possess a serious risk to workers if proper precautions are not taken. The materials commonly used in pumps are nickel based alloys or Nickel Aluminium Bronze. These materials are chosen because of their strong corrosion resistance and excellent cavitation properties. In this report, the focus is to observe Ni-Resist Type 1, Ni-Resist Type D-4 and Nickel Aluminium Bronze under different salinity and different temperatures, to see the effect temperature and salinity have on the rate of corrosion. Scanning electron microscopy and energy dispersive X-ray spectroscopy are also conducted on the materials before and after corrosion to observe for any changes in morphology or elemental distribution. The weight loss of each material is calculated after the corrosion immersion and compared to see how each material corrodes at different salinities and temperatures. The results from this experiment show that corrosion rates generally increased at higher temperatures. In contrast corrosion rate generally decreased at higher salinities. The results from this experiment could possibly help the oil and gas industry by providing more information so that better decisions can be made during pump selection. This could also potentially help companies save more money and provide a safer environment for their workers as equipment failure rates will be lower.